Lived experiences of Badjao mothers - Alforque, Ariane Shyne O.; Enrile, Andrea Kaye B.; Pepito, Alyanna Sophia I.; Tagsip, Donnel Mark E.; Viodor, John Jeric A.
Parenting is highly valued in Philippines culture because the family is the focus of social life and influences both children and their parents. Despite years of research, the parenting practices of Badjao mothers remain unknown. This study investigated the lived experiences of Badjao mothers in the Badjao Community, Alaska Mambaling, Cebu City. This research employs expert-approved queries and applies Baumrind's four types of parenting styles. It utilized a qualitative research design and a phenomenological design. The information about the participants was collected accurately. Five people have been questioned using authorized data. In-depth interviews were used to capture the data and utilized convenience sampling. Based on the responses, the thematic analysis established codes and themes to address the problem statement. According to the findings, Badjao mother face a range of responsibilities and sacrifices in nurturing and supporting their children, providing for the basic needs, and ensuring their education. Furthermore, Badjao mothers were more likely to exhibit authoritative and permissive parenting styles. To establish and extensive range of perspectives, future research is encouraged to select participants based on age, socioeconomic status, and family size, and longitudinally investigate this.
Includes bibliographical references.
Thesis -- Cebu Institute of Technology University
Keywords: Motherhood; Academic theses